HUBUNGAN MINDFULNESS DENGAN KECEMASAN MASYARAKAT SELAMA PANDEMI COVID-19 - Arif Rakhman; Dwi Budi Prastiani; Isni Fauziyah (Poltekkes Kemenkes Bengkulu, 2022)
At the beginning of 2020, the world was shocked by the Coronavirus Disease-19. This phenomenon causes changes in various aspects of life, such as health, economic, social, psychological, cultural, and more. The psychological response experienced by the community is a feeling of anxiety about their health. Anxiety can be managed properly through full awareness and attention to the conditions that are happening. Thus, it does not cause mental health problems. A state of awareness and attention in this pandemic moment called Mindfulness. This study aims to determine the relationship between mindfulness and anxiety during the Covid-19 pandemic in the community. This is quantitative research with a descriptive correlation design and a cross sectional approach. The population of this study is adult in Jatimulya Village. The sampling technique that used was simple random with a total of 288 respondents. The data collection that used was Five Facets of Mindfulness Questionnaire and the Anxiety Questionnaire during the Covid-19 pandemic. The results of the Kendall's Tau b analysis obtained that p-value is 0.000 < 0.05. It can be concluded that there is a relationship between Mindfulness and Anxiety during the Covid-19 pandemic among Jatimulya Village community. Community should have a good mindfulness in order to create awareness and attention in managing anxiety. Keywords: mindfulness, anxiety, pandemic Covid-19